Assessment of the Impact of Tractor Noise Exposure on Operators and Bystanders - Beabu B. DUMKHANA; Dandison M. WALI (FUDMA Journal of Engineering and Technology, 2026)
Rising noise levels from agricultural machinery contributed to environmental and occupational health issues, adversely affecting machine operators. This study investigated the impact of noise on operators and bystanders during tillage operations. A field experiment covering 1.10703 acres of land was divided into three blocks, each with 9 subplots measuring 160 × 38 m, for a total of 27 treatments in a randomized complete block design (RCBD). The generated noise data were used to create noise distribution trends for different tractor speeds during ploughing, harrowing, and ridging operations. The findings showed that increasing tractor speed from 5 to 9 km/h raised noise levels from 54 to 83.3 dB, affecting individual performance and productivity. As recommended by NESREA in 2007, harrowing met the noise level of 70 dB, while ploughing and ridging were 83.3 dB. Regression analysis revealed strong correlations (r² = 0.8073–0.995) between setback distance and noise reduction. This study has shown that tractor operators may experience temporary hearing loss when leaving the work environment in addition to cognitive fatigue.
Keywords: Agricultural machinery, noise exposure, setback distance, hearing impairment.